The Middle Jurassic and Early Cretaceous basalt-radiolarian chert association from the Tekelidağ Mélange, eastern İzmir-Ankara-Erzincan suture zone (northern Turkey). (March 2020) - Özkan, Mutlu; Çelik, Ömer Faruk; Soycan, Havva; Çörtük, Rahmi Melih; Marzoli, Andrea
Abstract: Basaltic and deep-sea sedimentary rocks are widely exposed in the Tekelidağ Mélange, eastern part of the İzmir-Ankara-Erzincan (İAE) suture zone. In this study, we present petrogenetic features of the basaltic rocks and new micropalaeontological data from the radiolarian cherts. The basaltic rocks are divided into two different groups based on whole-rock geochemistry data. The first group of basaltic rocks displays MORB-like geochemical characteristics. The second group exhibits island-arc tholeiite (IAT) geochemical characteristics. The cherts, which coexist within the basaltic rocks, yielded Middle Jurassic to Early Cretaceous radiolarian assemblages. Late Bajocian (Middle Jurassic) to Tithonian (Late Jurassic) ages were obtained from the radiolarian cherts observed within the MORB-type basalts belonging to the first group. On the other hand, the supra-subduction zone (SSZ)-type basalts belonging to the second group are associated with upper Aalenian (Middle Jurassic) and lower Aptian (Lower Cretaceous) radiolarian cherts. The new Middle–Late Jurassic and Early Cretaceous radiolarian dates and MORB- and SSZ-type basaltic rocks are consistent with radio-isotopic ages previously obtained from ophiolites and ophiolitic mélanges along the İAE suture zone. The radiolarian ages associated with basaltic rock data indicate that the occurrence of the MORB- and SSZ-type magmatism were simultaneous. The coeval IAT and MORB-like basalt generation inferred to occur in the SSZ environment similar to the South Sandwich back-arc basin system from South Atlantic Ocean, the Mariana Trough (e.g., Fiji and Tonga basin) from the Western Pacific and Coast Range Ophiolite from California. Graphical abstract: Image 1 Highlights: The radiolarian assemblages indicate to Middle Jurassic to Early Cretaceous ages. The basaltic rocks display MORB-like and SSZ-type geochemical characteristics. The MORB- and SSZ-type magmatism are contemporaneous. The basaltic rocks were occurred in the back-arc basin from the SSZ environment.